Knowledge, attitude and practice related to eye donation among donor’s and recipients’ family in Ahmedabad: a cross sectional study - Patel, Pritesh G.; Brahme, Keyur M.; Shringarpure, Kalpita S.; Bhatt, Rajshree (International Journal Of Community Medicine And Public Health, 2019)
Background: India shoulders the largest global burden of blindness. Despite all the advances of science, there is no artificial substitute invented so far to replace human cornea. This study was conducted to assess the knowledge, attitude and practice about eye donation among the eye donors’ and recipient’s family. Methods: A community based cross sectional study was conducted from January 2011 to December 2011 in Ahmedabad city, Gujarat. Eighty-one eye donors and 127 eye recipients using pre-designed and pre-tested proforma was finalized to collect the information from the participants either by home visit (in city) or by telephonic or e-mail interview. Data was entered and analyzed in MS Excel 2007 and Epi info7 software. Knowledge, attitude and practice were expressed as proportions. Results: A total of 81 eye donors and 127 eye recipient’s relatives were interviewed. Doctor or hospital was the most common source of knowledge regarding eye donation for both eye donors (68, 83.95%) and eye recipients (113, 88.97%). In this study 11 (13.58%) eye donors and 4 (3.15%) eye recipients were regular blood donors showing their positive attitude. Only nine (11.11%) donations were done by either donor’s personal will or by already pledging. Among our participants 68 (83.95%) family members had closed the eye lids of the donor after death, 39 (48.15%) had switched off fan of the room after death. Conclusions:Relatives of eye donors and eye recipients are willing to pledge for eye donation after death. Media and medical person was the mainstay in imparting knowledge to the participants. The relative of the donors are well versed with various aspect of preserving eyes after the death of donor compared to those recipients.